CHARLES DICKENS:A LITERARY TITAN OF THE VICTORIAN ERA - Kholiqjonova Zulkhumor; Kenjayeva Muxlisa Bahodirovna (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation: This article gives information about Charles Dickens, a prominent figure of the Victorian era, remains one of the most celebrated and influential novelists of all time. His extensive literary contributions, characterized by vivid characters, intricate plots, and insightful social commentary, continue to captivate readers and inspire writers today. This exploration delves into Dickens's life, major works, key themes, and lasting impact on literature and popular culture. His novels, such as Oliver Twist, A Christmas Carol, and Great Expectations, offer poignant reflections on social injustices, poverty, and the human condition, solidifying his position as a literary titan whose legacy endures.